ACTIVITIES OF LEGAL CLINICS UNDER MARTIAL LAW - Bohatiuk, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to investigate the pecularities of the activity of legal clinics under martial law. Research methods: cognitive-analytical, comparative-legal analysis, objective truth, etc. These methods make it possible to follow the dynamics of the creation of legal clinics, their types, the specifics of their activities at the current stage during martial law. Results: the peculiarities of the formation of legal clinics in the world and in Ukraine were analyzed, the activity of the Legal Consultation «Legal Clinic» of the National Aviation University (NAU) was highlighted in the system of clinical activity, the importance of mediation and informational and cultural activities of the legal clinic with the participation of students and consulting teachers was emphasized, focused attention to the importance of clinical education for the formation of future specialists in the field of law. Discussion: it was noted that there are a large number of internally displaced persons in Ukraine as a result of the military invasion, who need legal assistance in the matter of obtaining the status of IDPs, fixing the damages caused as a result of the loss of property, providing assistance to people with disabilities, pensioners and other vulnerable categories of Ukrainian citizens. Issues and clarifications regarding crossing the state border during martial law and staying in EU countries under the conditions of refugee or temporary status deserve special attention. The author noted that there is an urgent need for clarifications regarding the conclusion, changes and termination of an employment contract under martial law. Accordingly, legal clinics that provide legal assistance in the period of military challenges to the specified categories of persons perform extremely important work for people, the state and society.